2017
DOI: 10.14202/vetworld.2017.748-751
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive assessment of gastrointestinal parasites infection in freeranging wild herbivores and adjoining livestock of Panna Tiger Reserve, Madhya Pradesh, India

Abstract: Aim:This study was conducted to know the epidemiology of gastrointestinal parasites of free-ranging wild herbivores and adjoining livestock of Panna Tiger Reserve, Madhya Pradesh, India.Materials and Methods:A total of 374 fecal samples from wild herbivores (Chital Axis axis - 123, Sambar Rusa unicolor - 94, Nilgai Boselaphus tragocamelus - 86, and Chinkara Gazella bennettii - 71) and 284 fecal samples of domestic herbivores (cattle - 118, buffalo - 78, and goat - 88) were collected from common grazing land an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Restricted data on the species diversity of the parasites of exotic ungulates (artiodactyls) in nature are available in literature. Most of the studies were carried out by coprological methods examining the animals from zoos and nature reserves where dissection of animals for parasitological studies was impossible (Epe et al, 2001;Farooq et al, 2012;Vadlejch et al, 2015;Mir et al, 2016;Sengar et al, 2017). Th erefore, we were not able to collect enough data to perform reliable comparative analysis of the parasite diversity of ungulates kept in the Askania-Nova Reserve and under natural conditions.…”
Section: Discussionmentioning
confidence: 97%
“…Restricted data on the species diversity of the parasites of exotic ungulates (artiodactyls) in nature are available in literature. Most of the studies were carried out by coprological methods examining the animals from zoos and nature reserves where dissection of animals for parasitological studies was impossible (Epe et al, 2001;Farooq et al, 2012;Vadlejch et al, 2015;Mir et al, 2016;Sengar et al, 2017). Th erefore, we were not able to collect enough data to perform reliable comparative analysis of the parasite diversity of ungulates kept in the Askania-Nova Reserve and under natural conditions.…”
Section: Discussionmentioning
confidence: 97%
“…Prior investigations suggested that parasites involving an intermediate host, as trematodes or cestodes, are more difficult to develop in zoos [ 4 ]; then those having a direct life-cycle are highly prevalent in captivity, especially parasites capable of surviving for long periods in the environment as strongyles or ascarids [ 5 7 ]. Clinical signs attributable to parasites are seldom observed in captive animals, which might point that subclinical infections develop in most of cases [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the wild animals are endangered and already at the verge of extinction due to habitat destruction (forest fire), loss of genetic diversity, improper feeding and hunting (Sengar et al ., 2017). The pace of this mechanism is further exacerbated by many diseases caused by a variety of pathogenic agents including parasites.…”
Section: Resultsmentioning
confidence: 99%